Estimation of Diffuse Solar Radiation from Clearness Index for Multan, Southern Punjab, Pakistan - M. Rashid Tanweer,; Firoz Ahmad,; Zaheer Uddin,; Saif Ur Rehman ,; Intikhab Ulfat, (Journal of Basic & Applied Sciences, 2016)
Empirical correlations have been developed for Multan for the estimation of Diffuse Solar Radiation (DSR) as a function of clearness index (KT). The diffuse solar radiation are also estimated by the relationship as given by Liu and Jorden, Page and Iqbal. All these correlation shows a peak value of diffuse solar radiation for the months of July & August (monsoon months). The diffuse to global (total) radiation ratio is 0.317. The presently developed correlation are fine agreement with the result obtained by earlier models. It is inferred from the result that solar energy has bright prospects as far as its application and utilization is concerned. Empirical correlations have been developed for Multan for the estimation of Diffuse Solar Radiation (DSR) as a function of clearness index (KT). The diffuse solar radiation are also estimated by the relationship as given by Liu and Jorden, Page and Iqbal. All these correlation shows a peak value of diffuse solar radiation for the months of July & August (monsoon months). The diffuse to global (total) radiation ratio is 0.317. The presently developed correlation are fine agreement with the result obtained by earlier models. It is inferred from the result that solar energy has bright prospects as far as its application and utilization is concerned.